Implementation of Panca Curiga as a Method of Interpretation of Rumpaka Texts in Sundanese Culture - Gardapandawa, Budi Setiawan; Wastap, Jaeni B; Saleh, Sukmawati (Pascasarjana ISBI Bandung, 2023)
Panca Curiga is a method of Sundanese interpretation which is commonly used in understanding texts contained in art, especially in rumpaka songs. The existence of discourse about Panca Curiga in society until now has only been limited to discussion without scientific investigation. Efforts to understand how to interpret rumpaka, especially in art whose creator is unknown, has its own complexities. This can be seen from the rumpaka-rumpaka that appeared before the rise of artistic industrialization, for example in the Sundanese art of pantun or kawih kaulinan barudak. From the results of the study based on the application of Panca Curiga to the rumpaka pantun and kawih kaulinan barudak models, Panca Curiga actually has many similarities with the disciplines of interpretive methods such as Hermeneutics and Semiotics. Therefore, Panca Curiga can be an opportunity to be used to study rumpaka texts in Sundanese art.